DEVELOPMENT OF TRAINING BENCH FOR EFFECTIVE AND SAFE OPERATION OF BACKUP POWER AT INDUSTRIAL ENTERPRISES - V. R. Ivanovа; L. V. Fetisov (Известия высших учебных заведений: Проблемы энергетики)
The paper suggests the description and development of the demonstration stand «Automatic switch of stand-by power supply" for possibility of visual study and understanding of the multi-purpose power supply to ensure the reliability of electricity supply to consumers.